Meteorological conditions and behavioral spatial cognition: A critical review for decision-making amid environmental risk - Gregory J. DeGirolamo; Curtis L. Walker (Progress in Disaster Science, 2024)
Human visuospatial cognition plays a critical role in risk perception and resultant decision-making. In the context of hazardous meteorological conditions, risk communication aspiring to encourage desired protective action decision-making from the public must consider these cognitive factors. For messages encouraging protective action, the audience must receive, understand, and internalize the message before acting. Spatial processing of information may impact a person's understanding and is a precursor to taking protective action. This study proposes a critical assessment of relevant cognitive behavior literature into a synthesis with implications for hazardous weather risk communication. Socioeconomic and other demographic factors (e.g., education, social status, income) have a strong influence on risk perception and resultant behavior. For example, lower economic status individuals may perceive a lower risk when confronted with a particular situation relative to those with higher economic status and be more apt to take higher risks if the potential loss of income was perceived as a worse outcome for themselves individually. Additionally, previous research found age and other demographic-related differences (e.g., gender) in how people remember information when presented in a map-like versus first-person/ground-level perspective. Younger adults use a coordinate processing strategy while older adults use a categorical processing strategy. Both groups had a similar level of accuracy in recall; however, older adults were less accurate when recalling information from first-person perspective layouts. This suggests individual differences in how information presented on maps is processed (e.g., forecasts, hazardous weather alerts) compared to personal perception of the weather when it is experienced. Perceptual differences could result in increased public exposure to dangerous conditions otherwise believed, or perceived, to be safe.